Exposure to polycyclic aromatic hydrocarbons in urban environments: Health risk assessment by age groups - Tavera Busso, Iván (2014)
A detailed investigation was conducted into the concentration of polycyclic aromatic hydrocarbons (PAHs) associated with PM10 particles collected during 2012 in an urban area in Cordoba, Argentina. Their composition was studied and the lifetime lung cancer risk resulting from exposure to total and individual PAHs was estimated. Samples of PM10 were collected daily on fiber glass filters with PAHs being extracted with methylene chloride and analyzed by HPLC. Mean PAH concentrations were higher during autumn and winter. In contrast, during warm months, high ambient temperature and wind speed contributed to a decrease in the PAH ambient concentrations. The PAH levels found in the present study were within the range of those reported in other polluted urban areas. However risk factors calculated for exposure to individual and cumulative PAHs exceeded the carcinogenic benchmark level of 1x10−6 early in childhood, implying that these PAH concentrations represent a serious risk to public health.